(SIN^8X-5 SIN^5X+SINX)COSX DX

I need the answer to this, because I have tried so many times and cannot figure it out.

1 answer

I infer from the presence of DX that you want

∫(sin^8(x) - 5sin^5(x) + sin(x)) cos(x) dx

if you let u = sin(x), then du = cos(x) dx you have

∫(u^8 - 5u^5 + u) du

that's dead easy, using thge power rule:

1/9 u^9 - 1/6 u^6 + 1/2 u^2 + C

now change all the u's back to sin(x) and you're done
Similar Questions
  1. Simplify #3:[cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [cosx-(sin90cosx-cos90sinx)sinx]/[cosx-(cos180cosx+sinx180sinx)tanx] =
    1. answers icon 1 answer
  2. How do you simplify:(1/(sin^2x-cos^2x))-(2/cosx-sinx)? I tried factoring and creating a LCD of (sinx+cosx)(sinx cosx)
    1. answers icon 2 answers
  3. tanx+secx=2cosx(sinx/cosx)+ (1/cosx)=2cosx (sinx+1)/cosx =2cosx multiplying both sides by cosx sinx + 1 =2cos^2x sinx+1 =
    1. answers icon 0 answers
    1. answers icon 5 answers
more similar questions